Using passive acoustic monitoring to estimate northern spotted owl landscape use and pair occupancy - Cara L. Appel; Damon B. Lesmeister; Adam Duarte; Raymond J. Davis; Matthew J. Weldy; Taal Levi (Ecosphere, 2023)
Abstract Managing forests for biodiversity conservation while maintaining economic output is a major challenge globally and requires accurate and timely monitoring of imperiled species. In the Pacific Northwest, USA, forest management is heavily influenced by the status of northern spotted owls (Strix occidentalis caurina), which have been in continued population decline for the past four decades. The monitoring program for northern spotted owls is transitioning from mark–resight surveys to a passive acoustic framework, requiring development of alternative analysis approaches. To maintain relevance for conservation and management, these analyses must accurately track underlying population changes, identify responses to disturbance, and estimate occupancy of owl pairs. We randomly selected and surveyed 5‐km2 hexagons for 6 weeks using passive acoustic monitoring in the Olympic Peninsula of Washington and the Oregon Coast Range during the 2018 spotted owl breeding season. We used a convolutional neural network to identify spotted owl calls, followed by logistic regression to determine the sex of vocalizing owls to assign pair status. We implemented multistate occupancy models to estimate probabilities of detection, species‐level landscape use, and pair occupancy of spotted owls. We also quantified detections of barred owls (Strix varia), a congeneric competitor and important driver of spotted owl population declines. The overall rate of hexagon use by spotted owls was estimated at 0.21 (SD 0.04) after adjusting for imperfect detection, and pair occupancy was 0.07 (SD 0.02). The probability of detecting a pair (i.e., both female and male) during a weekly occasion was relatively low (0.03, SD 0.01), indicating that true pair occupancy was between 1.3 and 4.1 times greater than the proportion of hexagons with observed pair detections. Barred owls were ubiquitous, with a naïve occupancy rate of 0.97. The intensity of calling by barred owls had a weak, negative effect on the probability of spotted owls being paired when present but had little measurable effect on their detectability. This work establishes a framework that may be effective for spotted owl population monitoring and illustrates that pairs have very low detection probability, which—combined with increasingly low numbers of spotted owl pairs—is an important consideration for conservation and management.